Digital Flipbook Ecosystem (DFE) Based on Problem-Based Learning (PBL) to Improve Scientific Attitudes (Journal of Science Learning, 2026)
Digital Flipbook Ecosystem (DFE) on Problem-Based Learning (PBL) has been applied through the biology learning process to enhance students’ scientific attitudes towards ecosystem learning material. This learning model utilizes real problems in the surrounding environment as a trigger for scientific activities, so that students are trained to be able to be open-minded, work together, have a high level of curiosity, respect data, be sensitive towards the environment, be critical, and demonstrate perseverance. The study results showed that using PBL-based DFE contributed significantly to growing and improving all dimensions of students’ scientific attitudes, especially in open-mindedness, curiosity, and willingness to cooperate (work in a team). Problem-based learning visualized through DFE has been proven to increase motivation and active participation and strengthen students’ scientific behavior consistently in the biology learning process.